Effect of the addition of psyllium (Plantago Ovata Forsk) on the total and bioaccessible concentration of the minerals sodium and potassium in frozen banana pulp (Research, Society and Development, 2021)
Increased blood pressure is one of the main risk factors for cardiovascular disease. The World Health Organization (WHO) recommends that sodium intake should be moderate and potassium intake can be increased, as its intake is associated with a lower incidence of cardiovascular disease. Banana is a fruit rich in potassium and has large post-harvest losses due to its perishability. The production of frozen pulps is an alternative to reduce these losses. To add nutritional and functional benefits to the fruit pulp, it is possible to add soluble fiber, since its high intake is known to have a protective effect against cardiovascular disease and its intake by individuals does not meet the recommended minimum. There is evidence that psyllium dietary fiber contributes to lowering blood pressure, lowering cholesterol, lowering blood glucose and its incorporation into foods may offer health benefits such as preventing high blood pressure. Knowing that sodium and potassium intake is related to blood pressure, this study aimed to investigate the content of the minerals sodium and potassium in frozen banana pulp added with psyllium and to verify the concentrations of bioaccessibility in in vitro digestion. Our results showed that the addition of psyllium contributed to an increase in the content of the minerals potassium and sodium and that after the simulated digestions we verified that the final concentrations of the mineral potassium are in agreement with other results present in the literature, we also saw that despite increasing the sodium content, the final concentration of the dialysate (which would be absorbed by the human body) was 0.17%, being very low and ideal for preventing high blood pressure.